The Effect of Inflation, Interest Rates and Exchange Rates on Company Value (Case Study on Registered Banking Institutions on the Indonesia Stock Exchange) - Hiendrawati Hiendrawati; Arifuddin Mas'ud; Ummy Kalsum; Muh. Nur (Syntax Idea)
This research aims to determine the effect of inflation, interest rates and exchange rates on company value using data from the financial reports of companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The type of data used is quantitative data. The data source used is secondary data. The analytical tool used in panel data linear regression is EViews version 10. Simultaneous research results of the variables Inflation, Interest Rates and Exchange Rates have no influence on Company Value. Meanwhile, in partial testing, the variables inflation, interest rates and exchange rates have no effect on company value in banking institutions listed on the Indonesian Stock Exchange for the 2019-2023 period